Association between duration and type of androgen deprivation therapy and risk of diabetes in men with prostate cancer. Issue 12 (19th September 2016) - Crawley, Danielle; Garmo, Hans; Rudman, Sarah; Stattin, Pär; Häggström, Christel; Zethelius, Björn; Holmberg, Lars; Adolfsson, Jan; Van Hemelrijck, Mieke
Abstract : Androgen deprivation therapy (ADT) for prostate cancer (PCa) increases risk of type 2 diabetes (T2DM); however the association between types and duration of ADT has not been fully elucidated. We examined how type and duration of ADT affects risk of T2DM. Using data from Prostate Cancer database Sweden (PCBaSe) we investigated risk of T2DM in a cohort of 34, 031 men with PCa on ADT; i.e ., anti‐androgens (AA), orchiectomy, or gonadotropin‐releasing hormone (GnRH) agonists compared to an age‐matched, PCa‐free comparison cohort ( n  = 167, 205) using multivariate Cox proportional hazard regression. T2DM was defined as a newly filled prescription for metformin, sulphonylurea, or insulin in the Prescribed Drug Register. A total of 21, 874 men with PCa received GnRH agonists, 9, 143 AA and 3, 014 underwent orchiectomy. Risk of T2DM was increased in men in the GnRH agonists/orchiectomy group during the first 3 years of ADT [ i.e., 1 − 1.5 years HR: 1.61 (95%CI: 1.36 − 1.91)], compared to PCa‐free men. The risk decreased thereafter ( e.g ., 3 − 4 years HR: 1.17 (95% CI: 0.98 − 1.40)). Conversely, no increased risk was seen in men on AA (HR: 0.74 (95%CI: 0.65 − 0.84). The incidence of T2DM per 1, 000 person‐years was 10 for PCa‐free men, 8 for men on AA, and 13 for men on GnRH agonists/orchiectomy. Duration of ADT has a significant impact on risk of T2DM. With the peak after three years of treatment, our data indicates that men on ADT, even for a limited period of time, such as adjuvant to radiotherapy, are at increased risk of T2DM. Abstract : What's new? All treatments involve tradeoffs. For patients with prostate cancer, treatment with androgen deprivation therapy (ADT) can lead to an increased risk of type II diabetes. These authors set out to analyze how the duration of treatment, and the type of ADT, affect diabetes risk. They collected data on patients receiving three types of ADT: anti‐androgens, gonadotropin releasing hormone agonists, and orchiectomy, and compared them with age‐matched, cancer‐free controls. The risk of diabetes peaked after 3 years of treatment with GnRH agonists or orchiectomy. By contrast, patients receiving anti‐androgens showed no increase in diabetes risk relative to cancer‐free controls.